If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6x + -40 = 0 Reorder the terms: -40 + 4x + -6x = 0 Combine like terms: 4x + -6x = -2x -40 + -2x = 0 Solving -40 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -2x = 0 + 40 Combine like terms: -40 + 40 = 0 0 + -2x = 0 + 40 -2x = 0 + 40 Combine like terms: 0 + 40 = 40 -2x = 40 Divide each side by '-2'. x = -20 Simplifying x = -20
| 2-2-2-2-2-2-2-2-2=2 | | 6n-18=4n | | an=7+(n-1)(7) | | x-13=3x-27 | | X(x+10)=90 | | 0.06(y-9)+0.08y=0.18y-0.2 | | 13x+12=8x+7+4x+14 | | x-54=27 | | 55x+200=20+65x | | lnx=0.375 | | 6x^2+24=25x | | 27=6(9d-8) | | t+400=1230 | | 5x-9+7=-3 | | 10d+25q=45 | | sn=(n-2)180 | | M-3=23.8 | | M+z=bx | | 2.77= | | r-0.58=8.92 | | X^2-10=2x | | -2-(-3x-8)=4(-8z-7)+5 | | A=5.7 | | 7(p+2)+5p=60 | | 5x-9+7=3 | | 6x+5.4=19 | | 13-(4m+5)=4+2m-14 | | 10=-6.9+a | | 6(6x-1)=41 | | 4+3(2r+-8)=28 | | 2(4-9)-5= | | 2/7v-4/3=-3/2 |